Estimates Of Genetic Parameters For Body Weight And Shank Length In Aseel Chicken - Pandian, C.; Rajendran, R.; Sundaresan , A.; Omprakash , A.V. (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
Data on body weight, thigh length and shank length at eighth week from 237 Aseel birds were used for this study. The effects due to hatch and sex were found to be highly significant (P<0.01) on these traits except non-significant hatch effect on thigh length. The data were corrected for the fixed effects of hatch and sex for the estimation of heritability for these traits by paternal half-sib correlation method and Derivative Free Restricted Maximum Likelihood (DFREML) procedure. The heritability for these traits estimated by both the models were very low, non-significant and not different from zero.